Penubuhan Titik Tanda Sementara dengan Kaedah (Real Time Kinetic-Global Positioning System (RTK GPS) untuk Kelestarian Kerja - Nordin, Nor Azme; mohamed, sulzakimin; Abd Satar, Asiah (Research in Management of Technology and Business, 2022)
Land surveying technology plays an important role to ensure that all infrastructure development can be carried out quickly, save costs and energy and ensure the sustainability of work. The fast method known as RTK GPS is increasingly favored by surveyors because it adheres to the principle but in terms of accuracy and timing of measurements are still in doubt. In this study, the application of this rapid method was carried out with the establishment of temporary marking points for the purpose of survey work. Observations were made at 6 different locations/points of the environment to see the consistency and influence of location on the observation value. Observations were also done for 3 days and made at 4 different times, namely at night, morning, noon and evening. Observations of 5s, 20s and 30s were also made at each point involved. The results of the analysis have found that the establishment of temporary marking points is very suitable to be carried out in the afternoon and evening for all selected locations. While at other times the accuracy of the data is still within the permitted limits except at noon for locations on the high edges of tall buildings and in the forest. In terms of consistency, all selected control point station locations were also very consistent except at noon at locations next to tall buildings, on hills and in forests. In terms of observation time, the difference of 3s, 20s and 30s is not an issue because the difference is not very significant between the resulting observation values ​​and still within the allowable limits. Hopefully, this study can provide a better understanding to surveyors and stakeholders in the field of land surveying in order to ensure the sustainability of work is obtained.